2009 IEEE International Symposium on Industrial Electronics 2009
DOI: 10.1109/isie.2009.5222561
|View full text |Cite
|
Sign up to set email alerts
|

A study on simulator of human-robot cooperative manipulator for dental implant surgery

Abstract: Implant surgery is generally accepted as the good technique to replace the teeth completely. Development of CT(Computerized Tomography) and 3D visualization technique help to make the treatment plan and the surgical navigation assists the dentist during the intra-operative procedure. Although the navigation technique facilitates the positioning, the image guided adjustment of the angle cannot be attained easily in the dental surgery. In the paper, design and simulation of assistmanipulator for implant surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In addition to the assisted or automatic system, a team has constructed a human–machine collaborative dental implant system to fully utilize the advantages of both the surgeon’s experience and robot’s stability [ 27 ]. The design and simulation of a human–robot cooperative manipulator for implant surgery have also been studied [ 28 ]. To overcome the technical difficulties associated with oral implant treatment, a computer-aided oral implant system was introduced, including framing, modeling, preoperative 3D planning, registration, optical tracking, and real-time navigation systems [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the assisted or automatic system, a team has constructed a human–machine collaborative dental implant system to fully utilize the advantages of both the surgeon’s experience and robot’s stability [ 27 ]. The design and simulation of a human–robot cooperative manipulator for implant surgery have also been studied [ 28 ]. To overcome the technical difficulties associated with oral implant treatment, a computer-aided oral implant system was introduced, including framing, modeling, preoperative 3D planning, registration, optical tracking, and real-time navigation systems [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated the successful application of force guidance in the dental implant procedure, effectively compensating for slight misalignments caused by kinematic errors or patient motion [13], [14], [18]. This concept aligns with the principle of peg-in-hole assembly using force-guided robotic manipulators [30], [31].…”
Section: Introductionmentioning
confidence: 85%
“…Consequently, in contrast to the utilization of parallel kinematics mechanisms [13], serial mechanisms have been widely adopted in dental robotics [10]- [12], [14], [17]. Only a small number of systems still rely on the use of the RCM mechanism [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare [33] They can be used in healthcare to assist with surgeries or other medical procedures, such as nursing.…”
Section: Types Specific Applicationsmentioning
confidence: 99%